2022
DOI: 10.1007/s10964-021-01560-7
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction Development in the Transition to Adulthood: Differences by Gender and Immigrant Background

Abstract: Life satisfaction is crucial for healthy development into adulthood. However, it is yet largely unknown how life satisfaction develops in the transition to adulthood. This study examined life satisfaction development in this transition and paid special attention to differences between boys, girls, children of immigrants, and nonimmigrants. Unique longitudinal data of seven waves (2010–2018) of the Children of Immigrants Longitudinal Survey Germany were used. Respondents (N = 3757, 54% girls, 78% nonimmigrants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
3
13
1
Order By: Relevance
“…Regarding the differences in psychological variables in the normal weight and overweight/obese groups, the OWF showed significantly lower scores in life satisfaction, while the NWF showed a lower score in competence compared to OWM and NWM, respectively. These results are similar to those found in previous studies, in which females showed worse life satisfaction and competence than males [ 11 , 27 ]. A possible explanation could be that adolescence is a crucial stage in which adolescents are prone to teasing and taunting by their peers, with this situation more evident in females, who are more likely to suffer verbal-relational victimization, which hinders their participation in certain social activities and complicates their integration with the rest of their peers [ 89 , 92 ], thereby affecting their psychological state.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding the differences in psychological variables in the normal weight and overweight/obese groups, the OWF showed significantly lower scores in life satisfaction, while the NWF showed a lower score in competence compared to OWM and NWM, respectively. These results are similar to those found in previous studies, in which females showed worse life satisfaction and competence than males [ 11 , 27 ]. A possible explanation could be that adolescence is a crucial stage in which adolescents are prone to teasing and taunting by their peers, with this situation more evident in females, who are more likely to suffer verbal-relational victimization, which hinders their participation in certain social activities and complicates their integration with the rest of their peers [ 89 , 92 ], thereby affecting their psychological state.…”
Section: Discussionsupporting
confidence: 92%
“…Another relevant result is that between males and females with the same level of physical activity practice, no differences were found in life satisfaction or the satisfaction of basic psychological needs between AM and AF, but the differences were significant between SM and SF, with SF scoring lower. These results partially follow the line of previous research, which indicated that males showed higher scores than females in psychological variables [ 11 , 27 , 77 ], as they agree in the case of sedentary adolescents analyzed in this research, but in the case of active adolescents, no differences were found. These results highlight the importance of physical activity for female adolescents to achieve an adequate psychological state.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations